Global interconnect design in a three-dimensional system-on-a-chip. - Joyner, J.W (IEEE Transactions on VLSI systems)
A stochastic model for the global net-length distribution of a three-dimensional system-on-a-chip (3D-SoC) is derived. Using the results of this model, a global interconnect design window for a 3D-SoC is established by evaluating the constraints of: 1) wiring area; 2) clock wiring bandwidth; and 3) crosstalk noise. This window elucidates the optimum 3D-SoC global interconnect parameters for minimum pitch, minimum aspect ratio, and maximum clock frequency. In comparison to a two-dimensional system-on-a-chip (2D-SoC), the design window expands for a 3D-SoC to allow greater flexibility of interconnect parameters, thus increasing the guardbands to process variations. In addition, the limit on the maximum global clock frequency is revealed to increase as S2, where S is the number of strata. This increase in on-chip signaling rate, however, comes at the expense of I/O density, highlighting the need for new high-density-I/O packaging techniques to exploit the full potential of 3D-SoC.